SISTEM PERTANGGUNGJAWABAN PERKARA KORUPSI DALAM RANGKA PERCEPATAN PENYELAMATAN UANG NEGARA - Jawade Hafidz (Jurnal Dinamika Hukum, 2011)
Regulations governing the crime of corruption has changed several times. This is done to reach a modus operandi of various criminal acts of corruption and minimize the legal gaps that can be used as an excuse for the perpetrators of corruption to be able to detach himself from the shackles of law. Investigation, prosecution and examination before the court in a corruption case precedence over any other case to completion as soon as possible. In the Law of Criminal Acts of Corruption, the loss state is enough to capture perpetrators of corruption. Perpetrators of corruption have the right to prove that he did not commit corruption. Even so, the prosecutor still must prove the charges. Greater accountability of corruption, namely the possibility of imposition of penalty in absentia, the possibility of seizure of goods that had been seized for a defendant who has died before a verdict can not be changed again, the formulation of a broad scope of the offense, the expansion of the interpretation of the word "embezzle "the offense of embezzlement. Keyword : corruption, financial state, criminal responsibility